Sensual Relationship between the Individual and the World in the Literary Fiction by Žemaitė - Bleizgienė, Ramunė (Tautosakos darbai, 2016)
The basis of the article comprises the theoretical insights formulated by cultural anthropologist Michelle Z. Rosaldo and the phenomenological approach to the study of emotions. It aims at elucidating ways that emotional experience relates the bodily experience to the personal involvement into the network of social connections, participates in perception and understanding of the world, and defines patterns of personal activity. On the grounds of investigation of the preserved fragments of everyday speech and folklore compared with essays and fiction by Žemaitė, the author of the article describes the feeling of compassion and love, which binds the world and people together by mutual caring. Based on the analyzed sensual experience and expression of compassion and love, she reveals that personal feelings, tightly connected with the sensual (bodily) experience, form the basis for the social relationships, also correlating with the experience and understanding of the world in terms of perception of the self and the others. In the worldview model elaborated by Žemaitė, the world comes up as a certain order, supported by sensual and family relations. Just like in the social world, feelings are inseparable from the bodily bearing also in the natural world and pass from one body to another. Since human feelings belong to the mutual circle of emotions circulating between the world and individuals, the order in the social life depends on the similar feelings ensuring individual involvement into mutual relationships as in the nature. Obstructions in the flow of emotions, caused by and manifesting through rigid, immobile, unresponsive body, lack of empathy in relation to somebody’s feelings and inability of acting accordingly, or unrecognizing of the emotional bonds supporting the natural order, result in collapse of the personal life. Adequate sensual existence manifests itself not only through participation in the social relationship, but generally through being in the world and getting involved in the circle of emotional circulation. The analyzed examples of experience and expression of such feelings as compassion, love, and caring present evidence of such existence being based on human capacity to understand and recognize emotional states experienced by the others, as well as the ability to react and to respond, i. e. to experience emotions that are adequate to the situation and to act accordingly, including the ability to pass one’s emotions to others.
Keywords: -